Solar PV End-of-Life Waste Recycling: An Assessment of Mechanical Recycling Methods and Proposed Hybrid Laser and High Voltage Pulse Crushing Method - Amjad Ali; Muhammad Shahid; Sikandar Abdul Qadir; Md Tasbirul Islam; Muhammad Waseem Khan; Shoaib Ahmed (Resources)
This research article investigates the recycling of end-of-life solar photovoltaic (PV) panels by analyzing various mechanical methods, including Crushing, High Voltage Pulse Crushing, Electrostatic Separation, Hot Knife Cutting, Water Jet Cutting, and Magnetic Separation. Each method’s effectiveness in extracting materials such as glass, silicon, metals (copper, aluminum, silver, tin, lead), and EVA was evaluated. The analysis reveals that no single method is entirely sufficient for comprehensive material recovery. Based on the data analysis, a new hypothetical hybrid method, Laser and High Voltage Pulse (L&HVP), is proposed, which integrates the precision of laser irradiation with the robustness of high voltage pulse crushing. The laser irradiation step would theoretically facilitate the removal of the ethylene-vinyl acetate (EVA) encapsulant, preparing the materials for subsequent separation. The high high-voltage pulse crushing would then selectively fragment and separate the remaining components, potentially enhancing material recovery efficiency while minimizing contamination. The proposed approach is grounded in the observed limitations of existing techniques. This method aims to offer a more comprehensive and sustainable solution for solar PV module recycling. Further research and experimentation are necessary to validate the effectiveness of the L&HVP method and its potential impact on the field of solar PV recycling.